Peer-to-Peer with VB .NET - MacDonald, Matthew (Apress, 2012)
This book takes a practical look at peer-to-peer programming, without the hype. You'll explore how peer-to-peer designs work, learn fundamental peer-to-peer concepts, and master the .NET technologies you'll need to implement them. You'll also see that while some aspects of .NET are ideally suited for the peer-to-peer world, other high-level features haven't materialized yet. The emphasis in this book is on integrating peer-to-peer designs into your applications. This means that you'll focus on "hybrid" peer-to-peer designs that combine traditional solutions and peer-to-peer concepts to create new features such as instant messaging, resource sharing, and distributed computing.